Hadis Dan Resepsi Estetis Pesantren (Studi Kitab Fad’il Ramadan Karya Taufiqul Hakim) - Dzakiy, Ahmad Farih (Analisis: Jurnal Studi Keislaman, 2016)
This article describes Fada’il Ramadan, a book composed by a Pesantren leader in Jepara, Central Java, which has some unique features, particularly in the context of Hadits studies in the archipelago. The most unique character of the book is the aesthetic reception of some Hadiths about excellence of Ramadan (fada’il ramadan), as it represented within the content structure. Various hadits texts citated from some hadits literatur, are transformed into several stanzas of nazham, in  three  languages;  Arabic,  Javanese,  and Indonesian. This article tries to investigate the book. Starts on the breif summary of the author’s profile, it explain the identity of the book in addition to explore some uniqueness within the content, in the context of Hadits studies in the archipelago.